Genomic roadmaps for augmenting salinity stress tolerance in crop plants - Suprasanna, P.; Ghuge, S. A.; Patade, V. Y.; Mirajkar, S. J.; Nikalje, G. C. (Salinity Responses and Tolerance in Plants, 2018)
Serious antagonistic impacts of saline environment on plant growth, development, and yield are well established. In this regard, researchers and breeders have been utilizing many conventional as well as modern approaches to aid the pro- cess of developing salt-tolerant crops. Biotechnological tools have made the task of engineering salinity tolerance in plants easier. Currently, two major annexes are effectively employed to develop salt-tolerant crops, first, investigation of genetic variation via marker-assisted selection (MAS) and second the transgenic technology. Sustenance of plants under dynamically growth-limiting saline environment depends on alterations and/or switching between multiple biochemical pathways involved in response. A number of key regulatory genes have been successfully identified and characterized in this context which can be explored to serve the purpose of alleviation in salt-tolerant nature of plants. Several genomics-abetted approaches have been reported aiming toward improvement in growth and yield of crops under saline envi- ronment. Present chapter focuses on genomic roadmaps for augmentation of crop salt tolerance by various methods including MAS, transgenic breeding, manipulations in small non-coding RNAs, and genome editing. These approaches utilize key players involved in salinity-mediated plant defense mechanisms, such as ion transporters, osmolytes, antioxidants, transcription factors, signaling proteins, and microRNA. The chapter attempts to summarize the effective targets and exploration of these key entities to raise salt-tolerant plants through various genomics-related tools.